Activated biomass of the green microalga Chlamydomonas variabilis as an efficient biosorbent to remove methylene blue dye from aqueous solutions - Moghazy, Reda M (Water SA, 2019)
The raw and activated biomass of a green microalga, Chlamydomonas variabilis, were investigated as adsorbents for the removal of methylene blue (MB) dye from aqueous solutions. Chlamydomonas variabilis was isolated and cultivated to obtain a sufficient algal biomass. The collected biomass was first oven-dried and then activated by H2SO4. The results obtained showed that the optimum adsorption of MB occurred over 30 min of contact time at pH 7 and an biosorbent dose of 1.5 and 1.0 g·L−1 of dried biomass and activated biosorbent, respectively. Point of zero charge (pHpzc) was recorded at pH 6.8 and 6.9 for dried and activated biomass, respectively. The activated biomass was a more effective biosorbent than was the dried biomass: At a MB concentration of 82.4 mg·L−1, the minimum removal was greater than 98% using 1 g·L−1 activated biomass with a maximum adsorption capacity (qmax) of 115 mg·g−1, whereas at a MB concentration of 56.4 mg·L−1, the maximum removal did not exceed 80.8% using 1.5 g·L−1 raw biomass with a qmax of 18.3 mg·g−1. Furthermore, the Freundlich and Langmuir isotherm models of adsorption showed a better model fit when using activated biomass than when using raw biomass, with the former yielding R2 values greater than 0.9. The kinetic data suggest that the adsorption of MB follows the pseudo-second-order equation better than the pseudo-first-order one. This study demonstrates that the activated biomass of Chlamydomonas variabilis can be used as an effective biosorbent for the treatment of dye-containing wastewater streams.